Corrigendum (International Journal of Distributed Sensor Networks)
Jung June Lee, Kyung Tae Kim, Hee Yong Youn, Enhancement of congestion control of Constrained Application Protocol/Congestion Control/Advanced for Internet of Things environment, International Journal of Distributed Sensor Networks ; vol. 12, 11. First Published November 7, 2016. DOI: 10.1177/1550147716676274.